Technical Efficiency of Shrimp Fishery in South Carolina, USA - Vinuya, Ferdinand D. (2012)
The increased inflow of imported shrimp into the US has lowered shrimp prices in the marketplace and with it, ex-vessel prices received by shrimp fishermen. Proposed remedies are aimed at strategies to increase the prices received by domestic producers. This study looks into issues related to the production side by estimating the technical efficiency of South Carolina shrimp boat operators. Estimates using a stochastic production frontier method show that average efficiency is 46%. This finding has strong implications on the long-term survival and viability of the local shrimp industry as it continues to face competition from low-priced imports.